Small Renal Mass with Sarcomatoid Features - Oberle, Anthony D. (Curr Urol, 2020)
Interest in surveillance for small renal masses has expanded exponentially due to incidental detection with increased imaging. However, some of these small renal masses behave aggressively. Sarcomatoid pathology is associated with a worse prognosis. Traditionally, it has been thought of as a common pathway of dedifferentiation once a renal malignancy of any histology reaches a threshold size of approximately 3 cm. We report a case of a 65-year-old male with a 2 cm sarcomatoid renal cell carcinoma. To our knowledge, this is the smallest tumor with sarcomatoid differentiation reported in the literature.